Analysis of the glycosylation pattern of plant copper amine oxidases by MALDI‐TOF/TOF MS coupled to a manual chromatographic separation of glycans and glycopeptides. Issue 16 (12th July 2013) - Franc, Vojtěch; Řehulka, Pavel; Medda, Rosaria; Padiglia, Alessandra; Floris, Giovanni; Šebela, Marek; Guttman, Andras
<x xml:space="preserve">Abstract</x> The N‐glycosylation in pea seedling amine oxidase and lentil seedling amine oxidase was analyzed in the present work. For that purpose, the enzymes were purified as native proteins from their natural sources. An enzymatic deglycosylation of pea seedling amine oxidase by endoglycosidase H under denaturing conditions combined with its proteolytic digestion by trypsin was carried out in order to analyze both N‐glycans and "trimmed" N‐glycopeptides with a residual N‐acetylglucosamine attached at the originally occupied N‐glycosylation sites. The released N‐glycans were subjected to a manual chromatographic purification followed by MALDI‐TOF/TOF MS. MS and MS/MS analyses were also performed directly on peptides and N‐glycopeptides generated by proteolytic digestion of the studied enzymes. Sequencing of glycopeptides by MALDI‐TOF/TOF MS/MS after their separation on a RP using a microgradient chromatographic device clearly demonstrated binding of paucimannose and hybrid N‐glycan structures at Asn558. Such carbohydrates have been reported to exist in many plant N‐glycoproteins, e.g. in peroxidases. Although high‐mannose glycan structures were identified after the enzymatic deglycosylation, they could not be assigned to a particular N‐glycosylation site. The presence of unoccupied glycosylation sites in several peptides was also confirmed from MS/MS results.